Penentuan Personal Protective Equipment (PPE) Berdasarkan Koordinasi Over Current Relay (OCR) pada Sistem Distribusi - Filiana, Firilia; Tonce Kusuma Priyanto, Yun; Zarkasyi Efendy, Muhammad (SPECTA Journal of Technology, 2023)
Fault in the power system can pose a hazard not only to the equipment but also to the people working near it. Disturbances that can arise range from a short circuit that causes a spark, to a short circuit that can cause an arc flash. The arc hazard level can be estimated to determine the Personal Protective Equipment (PPE) that must be used by humans when working in electrified areas. In addition to the PPE level, arc current values can also be used to determine the safe distance between equipment and people. This research collects data on a distribution system of 65 buses which are the main distributors near the load, so their reliability must be high. System protection uses over current relay (OCR) and ground fault relay (GFR) to protect the system from 3-phase and 1-phase short circuit fault. The simulation results show that OCR and GFR can protect the system from short circuit disturbances that are close to the relay location. The higher the proximity to the source, the higher the PPE level and the safe distance between humans and electrical equipment.